Inattention in individual expectations - Yara de Almeida Campos Cordeiro; Wagner Piazza Gaglianone; Jo\~ao Victor Issler (EconomiA, 2017)
This paper investigates the expectations formation process of economic agents about inflation rate. Using the Market Expectations System of Central Bank of Brazil, we perceive that agents do not update their forecasts every period and that even agents who update disagree in their predictions. We then focus on the two most popular types of inattention models that have been discussed in the recent literature: sticky-information and noisy-information models. Estimating a hybrid model we find that, although formally fitting the Brazilian data, it happens at the cost of a much higher degree of information rigidity than observed. – – Este artigo investiga o processo de formaç\~ao de expectativas de inflaç\~ao de agentes econômicos. Utilizando o Sistema de Expectativas de Mercado do Banco Central do Brasil, percebemos que os agentes n\~ao atualizam suas projeç\~oes em todos os períodos e mesmo aqueles agentes que o fazem discordam sobre os valores previstos. Neste sentido, investigamos os dois tipos de modelos mais populares sobre inatenç\~ao discutidos na literatura recente: informaç\~ao com rigidez e informaç\~ao com ruído. Com base na estimaç\~ao de um modelo híbrido, concluímos que, embora formalmente o modelo seja capaz de se ajustar aos dados brasileiros, tal resultado ocorre ao custo de um grau muito maior de rigidez informacional do que o observado.
Keywords: C14; C52; D84; E37; 330; Expectations; Inflation; Imperfect information; Rational inattention